Metabolomics study on the effects of Orthosiphon Stamineus Benth. on streptozotocin-induced diabetic rat model - Ahmad Azam, Amalina (2015)
The main purpose of this research is to study the anti-diabetic effects of Orthosiphon stamineus Benth. Extract (OSE) in different solvent polarity (ethanol, ethanol: water,methanol, methanol: water and water) in streptozotocin (STZ)-induced diabetic rats by using metabolomics approach. The rat model of diabetic-induced by streptozotocin (STZ: 60 mg Kg-1) from which urine and serum used as the media to detect pathological changes during the development and curing of diabetes mellitus. The second objective is to develop a validated model between the chemical profile of extracts and anti-diabetic activity of induced STZ-diabetic rats that treated orally with OSEs within 14 days and Glibenclamide used as reference drug. Proton Nuclear Magnetic Resonance (1H NMR) spectra of the extracts, urine and serum were obtained and analyzed by multivariate data analysis (MVDA). Partial least square discriminant analysis (PLS-DA) of 1H NMR spectra disclosed metabolic pattern differences among groups where the related metabolic changes in urine and serum identified. OSE of water showed significantly (P < 0.05) reduction in urine glucose by 31.4% through PLS-DA of 1H NMR with changes nearing to the control group or similar to glibenclamide that reduced by 48.6%. The novelty of metabolomics approaches is their ability to give a broad overview of metabolites from complex biological samples. Interestingly, the spectroscopic data of urine STZ-diabetic rats revealed that glucose, allantoin, creatine, creatinine, and glutamate were near to normal group ranges after treatment. Furthermore, to propose the metabolism pathway affected by the OS treatment in diabetic rats, MetScape 3.0 software was used. Consequently, several metabolic pathways like carbohydrate, lipid, and amino acid metabolism have been affected during the treatment period. This study suggests that OSE of water may be beneficial in treating the hyperglycemic condition as it acts in a better way compared to glibenclamide drug. The significantly higher intensity of purine metabolites (allantoin) detected in OSE water indicates an increased in glomerular filtration rate that prove the ability in helping kidney function.